EVALUATION OF USE OF DIARRHEA DRUG IN PEDIATRIC PATIENTS AT DOLAT RAYAT HEALTH CENTER KARO DISTRICT - Ismi Noer Fadilah; Hendri Kurniawan (PT. Radja Intercontinental Publishing, 2022)
Diarrhea is a condition in which there is an imbalance in absorption, secretion of water and electrolytes, resulting in a frequency disorder of defecation more than 3 times a day with liquid or semi-solid stools, with or without mucus or blood. Diarrheal disease is still a global problem with a high degree of morbidity and mortality in various countries, especially in developing countries, and is one of the main causes of high child morbidity and mortality in the world. This study aims to determine the profile and rationality of using diarrhea drugs in pediatric patients at the Dolat Rayat Health Center, Karo Regency. This research was conducted using a retrospective descriptive method. The results of the study from the Dolat Rayat Health Center in Karo Regency showed that of the 235 patients who suffered from diarrhea the most were men (63-83%) and at the age of 2 years old infants (48.51%) with an average per patient of 1.28 drug items. The most widely used type of diarrhea drug was zinc (62.67%) in the form of syrup (54.67%). The rationality for using diarrhea medicines based on the 2011 Indonesian Ministry of Health guidelines includes the criteria for right indication (100%), right drug (100%), right patient (99.15%), and right dose (96.17%). Most of the use of diarrhea drugs in pediatric patients at the Dolat Rayat Health Center in Karo Regency is rational.